Student-centered teacher responses to student behavior in the classroom: A systematic review - Karasova, Jirina; Nehyba, Jan (Frontiers in Education, 2023)
Introduction Effective communication skills are essential for successful behavior management in the classroom. Teachers who can respond proactively and in a student-centered manner can create a positive and productive learning environment. However, the empirical support for student-centered communication practices in behavior management is limited. Methods To address this gap, a systematic literature review was conducted to identify the characteristics of student-centered behavior management strategies that lead to lower behavior problems and increased student engagement. The review utilized a PRISMA protocol to ensure the rigor of the study selection process. Results Five main categories were identified that characterize student-centered behavior management responses. A table of 24 communication strategies was presented based on the findings of the review. The study also discussed the further impact of these strategies on student motivation, learning outcomes, responsibility, and interpersonal classroom climate. Discussion The findings of this study highlight the importance of effective communication skills in behavior management and provide valuable insights for teachers to improve their practice. By implementing these student-centered communication strategies, teachers can manage the classroom effectively, creating a more positive and productive learning environment and supporting students in achieving better learning outcomes.